PERAN PEMERINTAH DAN MASYARAKAT DALAM PENYELENGGARAAN TV KABEL DI KOTA PEKANBARU TAHUN 2015-2016 - Lufia Alaina; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The title of this research is the role of Government and Society in the Implementation of Cable TV in Pekanbaru City Year 2015-2016 Based on the discovery of the phenomenon that occurred in the field is still the Cable TV Company that is merely licensed Broadcasting Implementation (IPP) but have already quoted premiums paid to thousands of customers Pekanbaru like Hope Blooms Multi Vision and Vision, and the persistence of the Cable TV company that is operational is not taking care of broadcast licenses but has long operated the information found that although not currently have approval Cable TV company has been able to encompass thousands of customers in the city of Pekanbaru. The type used in this research is descriptive qualitative survey techniques. Data collection techniques used in this study was observational, a note of Field, documentation and interviews with informants research. Location of the research conducted at the Regional Office of the Indonesian Broadcasting Commission (Commission) Riau.Based on the results of the analysis of the research data in order to uncover and answer research questions related to the role of government and the public in the administration of cable TV in the city of Pekanbaru can be concluded that the Government is KPID have done their job well but KPID also can not work with members are strictly limited to certain areas reach areas, the government is in dire need of cooperation with the community in which the participation of the public in supervising companies that are not good or are not abiding by the rules that have been set.Keywords: Role of Government, Society, Implementation of Cable TV.